2018
DOI: 10.1371/journal.pgen.1007360
|View full text |Cite
|
Sign up to set email alerts
|

Intronic PAH gene mutations cause a splicing defect by a novel mechanism involving U1snRNP binding downstream of the 5’ splice site

Abstract: Phenylketonuria (PKU), one of the most common inherited diseases of amino acid metabolism, is caused by mutations in the phenylalanine hydroxylase (PAH) gene. Recently, PAH exon 11 was identified as a vulnerable exon due to a weak 3’ splice site, with different exonic mutations affecting exon 11 splicing through disruption of exonic splicing regulatory elements. In this study, we report a novel intron 11 regulatory element, which is involved in exon 11 splicing, as revealed by the investigated pathogenic effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 38 publications
2
24
0
1
Order By: Relevance
“…While the nucleotide substitutions that were found in this region are located in intron 2, and do not change the amino acid sequence, it is possible that these substitutions might still influence FABP4 expression. For example they might affect the splicing of mRNA or be linked to variation elsewhere in a regulatory region (e.g., a miRNA binding site or enhancer binding site), or the 5 -UTR or 3 -UTR regions (UTR is untranslated region), that subsequently affects expression of the amino acid sequence (Wessagowit et al, 2005;MartõÂnez-Pizarro et al, 2018). Previous reports have demonstrated associations between genetic variation in FABP4 and carcass traits, meat quality traits, and fatty acid composition in adipocytes (Ardicli et al, 2017;Yan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…While the nucleotide substitutions that were found in this region are located in intron 2, and do not change the amino acid sequence, it is possible that these substitutions might still influence FABP4 expression. For example they might affect the splicing of mRNA or be linked to variation elsewhere in a regulatory region (e.g., a miRNA binding site or enhancer binding site), or the 5 -UTR or 3 -UTR regions (UTR is untranslated region), that subsequently affects expression of the amino acid sequence (Wessagowit et al, 2005;MartõÂnez-Pizarro et al, 2018). Previous reports have demonstrated associations between genetic variation in FABP4 and carcass traits, meat quality traits, and fatty acid composition in adipocytes (Ardicli et al, 2017;Yan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Hypothetically, in the presence of multiple enhancers, the actual splicing register might be determined by an equilibrium of exonic and intronic enhancer pulling forces. Furthermore, previous studies indicated that the concurrent binding of more than one U1 snRNP could also influence splice site selection through reciprocal stabilization of U1 snRNPs and SR proteins (Fernandez Alanis et al 2012;Hodson et al 2012;Martinez-Pizarro et al 2018).…”
Section: Allmentioning
confidence: 99%
“…Of note, this 5′ss mutation in both alleles of ELP1 gene is found in more than 99% of patients with Familial dysautonomia [38]. Finally, eU1s targeting an intronic region downstream of the authentic 5′ss caused some increase in Phenylalanine Hydroxylase exon 11 inclusion in the context of two pathological intronic mutations associated with Phenylketonuria [39]. It should be noted that for some eU1, the therapeutic potential of rescuing exon inclusion was subsequently confirmed in mouse models [35,37,38].…”
Section: Role Of U1 Snrnp In Splice Site Selection From a Distancementioning
confidence: 87%
“…In this review, we focus on a very important but less appreciated role of U1 snRNP in splice site selection from a distance. This review is inspired by recent studies employing engineered U1 (eU1) snRNPs that modulate splicing by annealing to sequences away from the 5′ splice sites [33][34][35][36][37][38][39]. All eU1s described here harbor mutations (base substitutions) within their 5′-ends, which enable their annealing to the intended target sequences within pre-mRNAs.…”
Section: Introductionmentioning
confidence: 99%